2015
DOI: 10.7816/sed-03-01-01
|View full text |Cite
|
Sign up to set email alerts
|

A Research on the Determination of Prospective Music Teachers’ Academic Motivation Levels (Konya Sample)

Abstract: Araştırmanın amacı, müzik öğretmeni adaylarının akademik motivasyon düzeylerinin cinsiyet ve sınıf değişkenlerine göre incelenmesidir. Araştırmada veri toplama aracı olarak Türkçe adaptasyonu ve geçerlik güvenirlik çalışmaları Karagüven tarafından(2012) yapılan "Akademik Motivasyon Ölçeği" kullanılmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Another study conducted by Ergin and Karatas (2018), it was determined that the achievement focused motivation levels of the students tend to be high. In the research, aimed to find out the academic motivation levels of the prospective music teachers, Kucukosmanoglu (2015) reached to the result that the intrinsic motivations of the prospective teachers related to the achievement were at a high level. In the research by Taskesen (2019), it was found that the Academic Motivations of the prospective visual arts teachers were at a high level.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Ergin and Karatas (2018), it was determined that the achievement focused motivation levels of the students tend to be high. In the research, aimed to find out the academic motivation levels of the prospective music teachers, Kucukosmanoglu (2015) reached to the result that the intrinsic motivations of the prospective teachers related to the achievement were at a high level. In the research by Taskesen (2019), it was found that the Academic Motivations of the prospective visual arts teachers were at a high level.…”
Section: Discussionmentioning
confidence: 99%
“…The high AM of student teachers is very significant in terms of having the knowledge and skills that will support the personal and social development of individuals when they become teachers in the future (Küçükosmanoğlu, 2015).…”
Section: Academic Motivation (Am)mentioning
confidence: 99%
“…The high AM of student teachers is very significant in terms of having the knowledge and skills that will support the personal and social development of individuals when they become teachers in the future (Küçükosmanoğlu, 2015). Thus, it can be explained that student teachers' beliefs, attitudes and perceptions have a significant influence on the teaching process.…”
Section: Introductionmentioning
confidence: 99%